The influence of organic acids and fungicides on scotch pine and penduculate oak in forest nurseries - Шульга, Виктор Олегович; Левченко, Валерій Борисович (Technology audit and production reserves, 2013)
Recently, the problem of increasing the productivity of forests is solved not only by selection and genetic methods and fertilization, but also by using the phyto-pharmacological plant protection products — natural or synthetic compounds, which at low concentrations can lead to significant changes in the growth and development of plants. When growing the standard seedlings of Scotch pine in nursery conditions, they are massively affected by the pathogens of Fusarium spp., Alternaria spp., Botrytis spp. One of effective ways of increasing the resistance of plant material to these pathogens is treatment of seeds and seedlings with solutions of anthranilic and acetylsalicylic acids.